Peluang dan Tantangan Pendidikan 4.0 dalam Implementasi Chat GPT pada Mahasiswa Ilmu Komunikasi di Kota Medan - Belindha Putri Purwantiningrum; Eunike Y.K Sembiring (ArtComm, 2024)
This research is entitled "Opportunities and Challenges of Education 4.0 in the Implementation of Chat GPT on Communication Science Students at the Universitas Sumatera Utara". This study aims to determine the challenges and opportunities in the era of education 4.0 in the implementation of Chat GPT on Communication Science students at the Universitas Sumatera Utara. The research method used in this research is qualitative phenomenology method. This research involved 5 (five) informants and 2 (two) triangulation informants who were selected according to the objectives and needs of the research using purposive sampling technique. The results of this study indicate that the implementation of Chat GPT in the era of education 4.0 requires all stakeholders to take part so that the use of Chat GPT can be a means of improving the quality of learning effectively without causing significant negative impacts. Students and educators need to have critical thinking skills, digital literacy, information literacy, and be wise in using information and communication technology. Proper use of Chat GPT can help prepare students to face real-world challenges in the education 4.0 era.